Exploring Jane’s and Pip’s identity formation in Charlotte Brontë’s Jane Eyre and Charles Dickens’s great expectations - Ramchandani Dheraj Vijay (2014)
This essay aims to explore the identity formation of both Jane and Pip from Charlotte Brontë’s Jane Eyre (1847) and Charles Dickens’s Great Expectations (1860) respectively to investigate whether or not the characters are a product of their own environment and explore why both authors designed them to be who they are and what they do in the novels. This will be done through the analysis of external and internal influencers of identity as well the study of the Bildungsroman genre that both authors use in the texts to deduce how these three factors affect the growth and maturation of these characters. This analysis will also involve the use of Jacques Lacan’s “mirror stage” theory, Erik Homburger Erikson’s Eight Ages of Man model and Jean Piaget’s Stages of Cognitive Development as frameworks to understand their identity development.